Genicular artery embolization for early-stage knee osteoarthritis: results from a triple-blind single-centre randomized controlled trial. (10th March 2023) - Landers, Steve; Hely, Rachael; Hely, Andrew; Harrison, Benjamin; Page, Richard S.; Maister, Nick; Gwini, Stella M.; Gill, Stephen D.
Abstract : Aims: This study investigated the effects of transcatheter arterial embolization (TAE) on pain, function, and quality of life in people with early-stage symptomatic knee osteoarthritis (OA) compared to a sham procedure. Methods: A total of 59 participants with symptomatic Kellgren-Lawrence grade 2 knee OA were randomly allocated to TAE or a sham procedure. The intervention group underwent TAE of one or more genicular arteries. The control group received a blinded sham procedure. The primary outcome was knee pain at 12 months according to the Knee injury and Osteoarthritis Outcome Score (KOOS) pain scale. Secondary outcomes included self-reported function and quality of life (KOOS, EuroQol five-dimension five-level questionnaire (EQ-5D-5L)), self-reported Global Change, six-minute walk test, 30-second chair stand test, and adverse events. Subgroup analyses compared participants who received complete embolization of all genicular arteries (as distinct from embolization of some arteries) (n = 17) with the control group (n = 29) for KOOS and Global Change scores at 12 months. Continuous variables were analyzed with quantile regression, adjusting for baseline scores. Dichotomized variables were analyzed with chi-squared tests. Results: Overall, 58 participants provided questionnaire data at 12 months. No significant differences were found for the primary and secondary outcomes, with both groups improving following the procedure. At 12 months, KOOS pain scores improved by 41.3% and 29.4% in the intervention and control groups, respectively. No adverse events occurred. Subgroup analysis indicated that the complete embolization group had significantly better KOOS Sports and Recreation, KOOS Quality of Life, and Global Change scores than the control group; 76.5% of participants who received complete embolization reporting being moderately or much better compared to 37.9% of the control group. Conclusion: TAE might produce benefits above placebo, but only when complete embolization of all genicular arteries is performed. Further comparative studies are required before definitive conclusions regarding the effectiveness of TAE can be made. Level of evidence: I Cite this article: Bone Jt Open  2023;4(3):158–167.